Langmuir–Blodgett artificial solid-electrolyte interphases for practical lithium metal batteries. (October 2018) - Kim, Mun; Ryu, Ji-Hyun; Deepika,; Lim, Young; Nah, In; Lee, Kwang-Ryeol; Archer, Lynden; Cho, Won
Abstract Practical lithium metal batteries require full and reversible utilization of thin metallic Li anodes. This introduces a fundamental challenge concerning how to create solid-electrolyte interphases (SEIs) that are able to regulate interfacial transport and protect the reactive metal, without adding appreciably to the cell mass. Here, we report on physicochemical characteristics of Langmuir–Blodgett artificial SEIs (LBASEIs) created using phosphate-functionalized reduced graphene oxides. We find that LBASEIs not only meet the challenges of stabilizing the Li anode, but can be facilely assembled in a simple, scalable process. The LBASEI derives its effectiveness primarily from its ability to form a durable coating on Li that regulates electromigration at the anode/electrolyte interface. In a first step towards practical cells in which the anode and cathode capacities are matched, we report that it is possible to achieve stable operations in both coin and pouch cells composed of a thin Li anode with the LBASEI and a high-loading intercalation cathode. A well-designed artificial solid-electrolyte interphase (ASEI) could help resolve multiple problems associated with the use of metallic Li anodes in batteries. Here, the authors develop a Langmuir–Blodgett method to produce an ASEI composed of functionalized graphene oxide with a compatible electrolyte formulation, which facilitates a stable cycling of Li metal batteries.